COMPARATIVE STUDY OF SPINACH LEAF NUTRIENT CONTENT FROM LEAF SPOT DISEASE CAUSED BY CERCOSPORA BETICOLA SACC.(1876) BEFORE AND AFTER DISEASE. (International Journal of Food and Nutritional Sciences, 2022)
Spinach is a leafy vegetable grown for its nutrient content. Throughout the world, it is consumed raw and cooked. Spinaciaoleracea L. is reported to be native to central Asia (Persia). Leaves and tender shoots are consumed fresh, processed, or mixed with other vegetables. Spinach (Spinaciaoleracea L.) is from the familyChenopodiaceae. Cercospora beticola Sacc. (1876),causes leaf spot disease on the leaves of spinach. When inoculated with isolated Cercospora, healthy leaves will develop the same leaf spot disease. Once the disease grew then, nutrients are isolated and compared with control spinach leafcontent.Cercosporabeticola, a pathogen, alters, and reduces the concentration of total carbohydrates 8.571 %, reducing sugar 22 %, dietary fibre 17.391 %, lipid 100 %, vitamin C 100 % and chlorophyll content 99.791 % of Spinach leaves. The protein level increases by 0.690 % and amino acids by 8.334 % in Spinach leaves.